Voter preferences, electoral promises, and the composition of public spending - Philip Keefer; Carlos G. Scartascini; Razvan Vlaicu (Inter-American Development Bank (IDB), 2020)
This paper proposes and empirically tests a new demand-side explanation for distortions in public spending composition. Voters prefer spending with certain and immediate benefits when they have low trust in electoral promises and high discount rates. The paper incorporates these characteristics of voter choices into a probabilistic voting model with public spending tradeoffs. In equilibrium, candidates promising larger allocations to transfers and short-term public goods are more likely to win elections in settings with low trust and high impatience. An original survey of individual-level preferences for public spending in seven Latin American capital cities provides observational and experimental evidence consistent with the model-derived hypotheses. Respondents reporting low trust in politician promises are more likely to prefer transfers to public goods; respondents with high discount rates prefer short-term to long-term spending. These patterns also appear in country-level data on spending outcomes from the last two decades.
Keywords: D72; H20; H50; O10; 330; Spending composition; Voter preferences; Trust; Discounting; Transfers; Public goods; Public investment